Ultra-low contact resistance in graphene devices at the Dirac point. (20th February 2018) - Anzi, Luca; Mansouri, Aida; Pedrinazzi, Paolo; Guerriero, Erica; Fiocco, Marco; Pesquera, Amaia; Centeno, Alba; Zurutuza, Amaia; Behnam, Ashkan; Carrion, Enrique A; Pop, Eric; Sordan, Roman
Abstract: Contact resistance is one of the main factors limiting performance of short-channel graphene field-effect transistors (GFETs), preventing their use in low-voltage applications. Here we investigated the contact resistance between graphene grown by chemical vapor deposition (CVD) and different metals, and found that etching holes in graphene below the contacts consistently reduced the contact resistance, down to 23 Ω ⋅ μ m with Au contacts. This low contact resistance was obtained at the Dirac point of graphene, in contrast to previous studies where the lowest contact resistance was obtained at the highest carrier density in graphene (here 200 Ω ⋅ μ m was obtained under such conditions). The 'holey' Au contacts were implemented in GFETs which exhibited an average transconductance of 940 S m −1 at a drain bias of only 0.8 V and gate length of 500 nm, which out-perform GFETs with conventional Au contacts.